Peran Keluarga dalam Meningkatkan Karakter Islami di SDN Tlogosari 1 - Siti Huzaimah; Nur Khosiah (Education Reserach Center, 2025)
This study aims to examine parental involvement in fostering Islamic character development among students at SDN Tlogosari 1, as well as the factors influencing it. The research employed a qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the level of parental involvement is significantly influenced by three main factors: educational background, occupational workload, and understanding of the importance of Islamic character education. Parents with higher educational backgrounds tend to be more active in accompanying their children and participating in school activities, while those with longer working hours rely more heavily on the school’s role in character formation. Furthermore, a strong understanding of the importance of Islamic values encourages greater synergy between families and schools. In conclusion, the success of Islamic character education requires close collaboration between schools and parents to ensure that Islamic values are consistently and sustainably instilled in students.